The Effectiveness of Respiratory System E-Module Based STEM to Improve Conceptual Understanding and Caring Attitudes towards the Dangers of Cigarettes in High School Students - Anggraeni, Diah Arum; Lisdiana, Lisdiana; Parmin, Parmin; Subali, Bambang (Unnes Science Education Journal, 2024)
An independent curriculum is a curriculum that requires active students. One way to make students active is through respiratory system e-module based STEM. This research aims to measure the validity, readability, and effectiveness of respiratory system e-module based STEM to improve conceptual understanding and caring attitudes towards the dangers of smoking in high school students.  Large-scale tests are carried out in classes XI SMA Negeri 1 Payung as much 70 students and SMA Negeri 1 Pulau Besar as much 50 students by using the results of conceptual understanding and assessing caring attitudes towards the dangers of smoking. The results of students’ conceptual understanding showed that average N-gain of 0.45 in the medium category. The assessment score for caring about the dangers of smoking among students obtained an average percentage score of 96.5% in the very good category. Based on the research results, it can be concluded that the respiratory system e-module  based STEM developed is valid and effective to improving conceptual understanding and caring attitudes towards the dangers of smoking in class XI.